A Wireless Spread Spectrum Communication System Using SAW Chirped Delay Lines - Springer, Andreas; Gugler, Wolfgang; Huemer, Mario; Koller, Rainer; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2001)
We report on the use of broad-band chirp signals for spread-spectrum communications in indoor and industrial environments. The well-known pulse compression technique associated with chirp signals is exploited to achieve a highly robust communication system. For the generation and compression of the chirp signals, surface acoustic wave delay lines fabricated from an LiTaO3-X112rotY substrate are used. Center frequency, bandwidth, chirp duration, and chirp rate are 348.8 MHz, 80 MHz, 500 ns, and ±40 MHz/μs, respectively. Different modulation schemes for chirp signals are introduced, the effects of nonlinearities, frequency drift, and temperature drift are addressed, and simulations and measurement results from a hardware demonstrator are presented for the use of π/4-differential quadrature phase-shift keying (DQPSK) modulation. A data rate of up to 40 Mb/s has been achieved experimentally and shows that the proposed system is highly robust against multipath effects
elib2cris::1512001600,springer2001a
Keywords: Wireless communication; Surface acoustic waves; Spread spectrum communication; Signal generators; Pulse compression methods; Robustness; Frequency; Phase modulation; Chirp modulation; Communication industry